Low-rank approximations of nonseparable panel models - Iván Fernández-Val; Hugo Freeman; Martin Weidner (Centre for Microdata Methods and Practice (cemmap), 2020)
We provide estimation methods for panel nonseparable models based on low-rank factor structure approximations. The factor structures are estimated by matrixcompletion methods to deal with the computational challenges of principal component analysis in the presence of missing data. We show that the resulting estimators are consistent in large panels, but suffer from approximation and shrinkage biases. We correct these biases using matching and difference-in-difference approaches. Numerical examples and an empirical application to the effect of election day registration on voter turnout in the U.S. illustrate the properties and usefulness of our methods.
Keywords: 330